COMPARISON OF ANTI-DIABETIC AND ANTI-OXIDANT ACTIVITY OF WILD AND CULTIVATED VARIETY OF RAUWOLFIA SERPENTINA - Chauhan, Saveena; Kaur, Amrinder; Vyas, Manish; Khatik, Gopal L (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: About 80% of world populations are still dependent on herbal plants. Rauwolfia is also one of the wonder drugs of India, which is used since ancient time. It contains a variety of compounds with antioxidant activity and other health benefits. A wild variety of rauwolfia is became endangered due to indiscriminate use. Hence, its cultivation and collection have been started to complete the demand of rauwolfia. Therefore, the study was designed to evaluate and compare the in vitro antioxidant and antidiabetic activity of the wild and cultivated plant of rauwolfia. Methods: The methanolic extract of wild and cultivated plant was subjected to the DPPH and alpha-amylase inhibition activity for antioxidant and antidiabetic activity, respectively. Result: The study revealed that the wild and cultivated variety of Rauwolfia serpentina does not have a significant difference in their antidiabetic and antioxidant activities. Conclusion: On the basis of the in-vitro studies, it can be concluded that cultivated variety of the plant can be used as a substitute for a wild variety of R. serpentina.